Influence of Practicum Venture Process on Engineering Students: Experience and Learning Outcomes of Entrepreneurship Course - Raju, G.Satheesh; Kumar, N.Suman; Sampath, L. (Journal of Engineering Education Transformations, 2025)
Entrepreneurship education is a challenge for the educators in delivering the outputs. The aim of this entrepreneurship course is to inculcate entrepreneurial mindset and encourage the students to pursue entrepreneurship as career. This paper discusses the practice adopted by the educators while teaching entrepreneurship to engineering students in the university. It is an evaluation and interpretation of the pedagogy used as well as the activity which is designed for the course. The implementation of the activity along with continuous evaluation followed and the output has been presented through this paper. While preparing the activity various practices adopted by universities were considered and activity named “practical venture” has been designed. This activity makes the students to run their own venture in the campus with all the support provided by the university. The intention of this activity is not to measure the success of the venture but to make the students undergo into the realistic environment which entrepreneur's go through. The students' teams are made to work on customer interviews, solution offered, developing market viable product (MVP), test marketing, financial planning and go to market strategy. A rubric has been constructed to assess the students learning from this course. The results of this paper can be used by the entrepreneurship educators in designing the entrepreneurial curriculum.